A Proposito Di Lorenzo Geri - Michele Lodone: Letteratura Medievale E Testi Profetici. Le Profezie in Versi Nel Trecento = ABOUT LORENZO GERI - MICHELE LODONE : MEDIEVAL LITERATURE AND PROPHETIC TEXTS. THE PROPHECIES IN VERSE IN THE THIRTEENTH CENTURY - Rotonda, Tavola (Rivista di storia del cristianesimo, 2022)
The article reports that on September 9, 2021, a presentation of the collective volume Lorenzo Geri-Michele Lodone, Medieval literature and prophetic texts was held online.